Drug-Coated Balloon Angioplasty and Debulking for the Treatment of Femoropopliteal In-Stent Restenosis: A Systematic Review and Meta-Analysis - Tong, Zhu (Biomed Res Int, 2020)
The purpose of this article was to compare the efficiency and safety of drug-coated balloon angioplasty (DCB) and atherectomy with percutaneous transluminal angioplasty (PTA) in patients with femoropopliteal in-stent restenosis (ISR). Pubmed, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) (all up to March 2019) were searched systematically. Trial sequential analysis (TSA) was conducted. 5 studies with 599 participants were included. Compared with PTA, DCB significantly increased the rate of patency (6 months: RR 1.65, 95% CI 1.30 to 2.09, P < 0.01; 12 months: RR 2.38, 95% CI 1.71 to 3.30, P < 0.01) and the rate freedom from target lesion revascularization (TLR) (6 months: RR 1.18, 95% CI 1.09 to 1.28, P < 0.01; 12 months: RR 1.56, 95% CI 1.33 to 1.82, P < 0.01) at 6 and 12 months follow-up, and the TSA results showed these outcomes were reliable. The rate of clinical improvement by ≥1 Rutherford category in the DCB group was higher than that in the PTA group (6 months: RR 1.35, 95% CI 1.03 to 1.75, P = 0.03; 12 months: RR 1.46, 95% CI 1.17 to 1.82, P < 0.01) at 6 and 12 months. There is no statistically difference of ABI, all-cause mortality, and incidence of amputation between DCB group and PTA group (MD 0.03, 95% CI -0.03 to 0.08, P = 0.40; RR 1.24, 95% CI 0.46 to 3.34, P = 0.67; RR 0.32, 95% CI 0.01 to 7.61, P = 0.48). Compared with PTA, the rate of patency and freedom from TLR in the laser atherectomy (LD) group was higher than that in the PTA group (patency: 6 months: RR 1.28, 95% CI 1.01 to 1.64, P < 0.05, 12 months: RR 2.25, 95% CI 1.14 to 4.44, P < 0.05; freedom from TLR: 6 months: RR 1.27, 95% CI 1.05 to 1.53, P = 0.01, 12 months: RR 1.59, 95% CI 1.12 to 2.25, P = 0.01) at 6 and 12 months follow-up. In conclusion, DCB and LD had superior clinical (freedom from TLR and clinical improvement) and angiographic outcomes (patency rate) compared with PTA for the treatment of femoropopliteal ISR. Moreover, DCB and LD had a low incidence of amputation and mortality and were relatively safe methods.